2014
DOI: 10.1002/mus.24057
|View full text |Cite
|
Sign up to set email alerts
|

Targeting therapy to the neuromuscular junction: Proof of concept

Abstract: Introduction:The site of pathology in myasthenia gravis (MG) is the neuromuscular junction (NMJ). Our goal was to determine the ability to direct complement inhibition to the NMJ. Methods: A single-chain antibody directed against the alpha subunit of the acetylcholine receptor was synthesized (scFv-35) and coupled to decay-accelerating factor (DAF, scFv-35-DAF). scFv-35-DAF was tested in a passive model of experimentally acquired MG. Results: Administration of scFv-35-DAF to mice deficient in intrinsic complem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…The rats treated with rCrry-Ig were rendered entirely resistant to EAMG induction and this effect was accompanied with a significant reduction in NMJ complement deposition (Hepburn et al, 2008). Likewise, the rats treated with scFv-35-DAF showed significantly lower clinical muscle weakness scores and a reduction of complement deposition compared to the nontreated control rats (Kusner et al, 2013).…”
Section: Inhibition Of the Whole Complement Systemmentioning
confidence: 98%
“…The rats treated with rCrry-Ig were rendered entirely resistant to EAMG induction and this effect was accompanied with a significant reduction in NMJ complement deposition (Hepburn et al, 2008). Likewise, the rats treated with scFv-35-DAF showed significantly lower clinical muscle weakness scores and a reduction of complement deposition compared to the nontreated control rats (Kusner et al, 2013).…”
Section: Inhibition Of the Whole Complement Systemmentioning
confidence: 98%
“…The MAC eventually causes severe focal damage to the postsynaptic membranes of NMJ. [33][34][35] In practice, eculizumab, a humanized monoclonal antibody that binds to C5, preventing formation of a C5b-induced MAC, can be prescribed for the treatment of generalized AChR-MG. 36 The second mechanism involved in the pathogenesis of AChR-MG has also been shown with animal models. These morphological changes attenuate postsynaptic sensitivity to the neurotransmitter due to the loss of AChR, resulting in diminished neuromuscular transmission and the manifestation of myasthenic symptoms.…”
Section: Animal Models Of Achr-mgmentioning
confidence: 99%
“…A randomized double blind, placebo-controlled crossover, multicenter phase 2 study of eculizumab in patients with refractory generalized MG has shown that the drug was effective in AChR-MG patients [88]. Complement inhibition localized at the neuromuscular junction has recently been achieved with a single-chain antibody directed against the alpha subunit of the AChR and coupled to decay accelerating factor (scFv-35-DAF), a complement regulator known to accelerate the decay of C3 and C5 convertases [89]. This proof of concept study may represent an elegant refinement of complement inhibition approach to circumvent systemic inhibition by localizing complement blockade at the site of the pathology.…”
Section: Autoimmune Diseases; the Example Of Mgmentioning
confidence: 99%